The impact of Facebook hate speech on the public A field study on a sample of Facebook users in Algeria - صلاح الدين عمراوي; يوسف مقعاش (International Journal of Social Communication, 2022)
This article addresses one of the most important issues that have become a major concern in the social system, represented by hate speech, which has taken an influential turn on the public, especially with the wide spread of Facebook users. This study aims to shed light on hate speech through its content circulating in Algeria, and the main mechanisms to confront this speech, and to update hate speech, and identify the impact of hate speech on the youth and Algerian society. In this context, this study highlights some of the forms and contents of hate speech spread on Facebook and its impact on the public in Algeria. The descriptive analytical method was used in this study based on the questionnaire form in the field, which was distributed to a sample of Facebook users in Algeria. The sample was estimated at 74 individuals across the states of the country, and the results of the study confirmed the correlation between hate speech via Facebook.